Impact of orthogonal exchange coupling on magnetic anisotropy in antiferromagnetic oxides/ferromagnetic systems. (2nd September 2016) - Kuświk, Piotr; Gastelois, Pedro Lana; Głowiński, Hubert; Przybylski, Marek; Kirschner, Jürgen
Abstract: The influence of interface exchange coupling on magnetic anisotropy in the antiferromagnetic oxide/Ni system is investigated. We show how interfacial exchange coupling can be employed not only to pin the magnetization of the ferromagnetic layer but also to support magnetic anisotropy to orient the easy magnetization axis perpendicular to the film plane. The fact that this effect is only observed below the Néel temperature of all investigated antiferromagnetic oxides with significantly different magnetocrystalline anisotropies gives evidence that antiferromagnetic ordering is a source of the additional contribution to the perpendicular effective magnetic anisotropy.